Strategi Pencegahan Missfile Pada Rekam Medis Dilihat Dari Unsur 5M di RSAU dr. Sukirman Lanud Roesmin Nurjadin Tahun 2021 - Doni Jepisah; Putri Yahya (Jurnal Rekam Medik & Manajemen Informasi Kesehatan, 2022)
In the medical record filling section of RSAU dr. Sukirman Air Base Roesmin Nurjadin in the last few days found 5 missfile events. Missfile is an error in placing medical records, incorrectly storing medical records, or not finding medical records in the storage section. The purpose of this study was to determine the missfile prevention strategy based on the 5M element at RSAU dr. Sukirman Air Force Base Roesmin Nurjadin. This type of research is descriptive with a qualitative approach. Methods of data collection using interviews and observation. Informants in this study amounted to 3 people, namely the head and staff of medical records. From the research conducted in the filling section, it was found that two medical record officers with a D III education level in Medical Records and Health Information who had worked for a long time ranged from 4-5 years. But have never received training from a hospital. There is no use of tracers, color codes, and expedition books, only outpatient register books. There is a budget for facilities and infrastructure as well as shelves. SOP for storing and retrieving medical records has been going well. An open medical record shelf made of wood and a medical record folder that is quite thick and has bones in it. We recommend that the hospital filling section use tracers and expedition books in order to minimize missfile events, conduct training for officers and increase the number of existing shelves so that medical records do not pile up and missfile events do not occur again.